2022
DOI: 10.1017/s0022149x22000025
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of leaf extract ofMoringa oleiferaLam. againstHaemonchus contortusandNacobbus aberrans

Abstract: In the present study, the nematicidal activity of a Moringa oleifera ethyl acetate leaf extract against the eggs and larvae of Haemonchus contortus and Nacobbus aberrans, nematodes of agricultural importance, was evaluated. The experimental design for the evaluation of the effects against both nematodes consisted of eight treatments (n = 4). Distilled water, Tween (4%) and a commercial anthelmintic agent (ivermectin, 5 mg/mL) were used as controls, and for treatments 4–8, the concentrations of the extract were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…En cuanto al fitol, ha sido reportado en el extracto etanólico de Petiveria alliacea como el principal metabolito con actividad insecticida contra ninfas Bemisia tabaci (Cruz-Estrada et al, 2013). El compuesto biológicamente más activo en el extracto de A. mexicana ha sido el ácido 9,12,15-Octadecatrienoico, (Z,Z,Z)-, que está reportado en el extracto de de etilo de Moringa oleifera como inhibidor en la eclosión de huevos y mortalidad de ninfas del 3er estadio de Haemonchus contortus y Nacobbus aberrans (Páez-León et al, 2022). Por último, el alcaloide 5,7,8,15-Tetrahidro-3,4-dimetoxi-6-metil[1,3]benzodioxolo [5,6-e][2]benzazecin-14(6H)-ona obtenido del extracto acuoso de A. mexicana, demostró actividad antiparasitaria sobre Plasmodium falciparum (Simoes-Pires et al, 2014).…”
Section: Resultados Y Discusiónunclassified
“…En cuanto al fitol, ha sido reportado en el extracto etanólico de Petiveria alliacea como el principal metabolito con actividad insecticida contra ninfas Bemisia tabaci (Cruz-Estrada et al, 2013). El compuesto biológicamente más activo en el extracto de A. mexicana ha sido el ácido 9,12,15-Octadecatrienoico, (Z,Z,Z)-, que está reportado en el extracto de de etilo de Moringa oleifera como inhibidor en la eclosión de huevos y mortalidad de ninfas del 3er estadio de Haemonchus contortus y Nacobbus aberrans (Páez-León et al, 2022). Por último, el alcaloide 5,7,8,15-Tetrahidro-3,4-dimetoxi-6-metil[1,3]benzodioxolo [5,6-e][2]benzazecin-14(6H)-ona obtenido del extracto acuoso de A. mexicana, demostró actividad antiparasitaria sobre Plasmodium falciparum (Simoes-Pires et al, 2014).…”
Section: Resultados Y Discusiónunclassified
“…In horses, it has been shown that bioactive compounds from plants can exert control over gastrointestinal parasites and that, in the case of nematodes (Strongylus sp., Trichostrongylus axei, Strongyloides westeri, and Parascaris equorum), the compounds with the highest activity against these parasites are phenols and tannins [105]. In this regard, it has been reported that the leaves of M. oleifera have the potential to combat nematodes [131], and according to what was reported by Mbogning-Tayo et al [132], the leaves of mature trees can inhibit the development and hatching of the eggs in 92.8 and 99.0%, and cause the mortality of the first and second instar larvae in 98.8 and 100.0%, at a dose of 5 mg mL −1 . Some researchers have attributed the antiparasitic activity mainly to the tannin content, but they are classified according to their chemical structure as follows: in condensed tannins, which are made up of complex compounds and are characterized by the presence of flavonoids, and in tannins, hydrolyzables that have a simple structure and contain smaller molecules, including gallic and ellagic acids [133].…”
Section: Antiparasitic Activity Of Moringa Oleiferamentioning
confidence: 99%
“…Studies involving ethyl acetate extract of moringa ( Moringa oleifera ) leaves showed a 90.7% inhibition of N. aberrans s.l. egg hatching at a concentration of 5 mg/mL, 12 h after treatment, with 100% J2 mortality achieved at 10 mg/mL, 24 h after treatment ( Páez-León et al., 2022 ). Sosa et al.…”
Section: Sustainable Strategies For Managementmentioning
confidence: 99%